Boosting Reading Skills and Motivation Through Video-Assisted Problem Based Learning Model : Meningkatkan Kemampuan Membaca dan Motivasi Belajar Melalui Model Pembelajaran Berbasis Masalah Berbantuan Video - Putri, Aulia Eka; Sulfasyah, Sulfasyah; Ratnawati, Ratnawati (Indonesian Journal of Innovation Studies, 2025)
General Background: Enhancing literacy and motivation in elementary education is a persistent priority in improving student learning outcomes. Specific Background: Problem-Based Learning (PBL), especially when integrated with multimedia resources like learning videos, has shown potential in fostering active engagement and comprehension. Knowledge Gap: However, empirical evidence remains limited regarding the simultaneous effects of PBL models aided by video on both reading comprehension and motivation among elementary students. Aims: This study investigates the effect of the PBL learning model assisted by learning videos on the reading comprehension skills and learning motivation of fourth-grade students in Cluster II, Mariso District. Results: Using a quasi-experimental nonequivalent multiple-group design with 56 students, results showed an improvement in reading comprehension from a pretest mean of 62.14 to a posttest mean of 78.21, and in learning motivation from 80.96 to 88.29. MANOVA analysis revealed a significant simultaneous effect (sig = 0.00 < 0.05). Novelty: This research demonstrates the dual effectiveness of video-assisted PBL not just on cognitive outcomes but also on affective dimensions. Implications: Findings highlight the potential of integrated multimedia-PBL strategies in enhancing educational quality in elementary schools. Highlights: Demonstrates PBL's impact on both comprehension and motivation. Uses video-assisted instruction in a real classroom setting. Shows significant results through MANOVA statistical analysis. Keywords: Problem-Based Learning, Reading Comprehension, Learning Motivation, Learning Videos, Elementary Education